HLF gene is a poor prognostic factor in acute myeloid leukemia patients with FLT3-ITD/NPM1 mutations undergoing hematopoietic transplantation - Xiaoyu Xu; Xinxin Ge; Airui Jiang; Jia Chen; Qiaocheng Qiu; Zixuan Ding; Mingqing Zhu; Jinlan Pan; Zixing Chen; Wenwen Du; Depei Wu; Suning Chen; et al. (PLoS ONE, 2025)
Acute myeloid leukemia (AML) patients with FLT3-ITD mutations were benefit from hematopoietic cell transplantation (HSCT) in the first complete remission. Previous research suggested that newly diagnosed AML patients with high allelic ratio (AR) of FLT3-ITD have unfavorable survivals, while newly diagnosed AML patients with lower FLT3-ITD AR and concomitant NPM1 mutations have favorable outcomes. In AML patients with FLT3-ITD, co-occurrence with DNMT3A, and NPM1 mutations (triple-mutated AML patients) have the worst prognoses, however, it is little known about how these mutations synergize in these triple-mutated AML patients. Here we showed that hepatic leukemia factor (HLF) gene was more highly expressed in triple-mutated AML patients than in those without the DNMT3A mutations. We found that HLF gene expressions had significant difference in triple-mutated and FLT3-ITD/NPM1 AML patients (double-mutated AML patients). Moreover, in DNMT3A mutated AML patients, correlated with high HLF gene expression, which may be itself associated with poor survival rate and drug resistance. Overall our data establish that HLF gene as a novel biomarker in this genetically defined the triple-mutated AML subgroup.